Nominalization in Applied Linguistics and Medicine: The Case of Textbook Introductions and Book Reviews - Jalilifar, Alireza; Elhambakhsh, Seyedeh Elham; White, Peter R. (Research in Language, 2018)
Drawing on Systemic Functional Linguistics, this study explored variational use of nominalization in 600 textbook introductions and 200 book reviews in applied linguistics and medicine. The nominalized expressions were identified in the texts, the frequencies of the nominalization types were counted, and eventually a chi-square test was administered. Analysis of nominalization patterns across the different informational/promotional moves revealed divergent patterns in the two disciplines but insignificant differences across the genres in focus. The density of nominalizations was acknowledged in the applied linguistics introductions and book reviews. However, functional variations in the use of nominalizations were found only in the introductions. As for the proportion of nominalization to grammatical metaphor, results demonstrated a lower tendency towards nominalizing scientific information in the medicine corpus. Further research is needed to see how nominalization is exploited in other genres and other disciplines.